A Plasticene Lexicon. (January 2020) - Haram, Linsey E.; Carlton, James T.; Ruiz, Gregory M.; Maximenko, Nikolai A.
Abstract: As plastic pollution in the environment has increased rapidly in the last half century, so too has the study of the effects of plastic on marine, aquatic and terrestrial ecosystems. From this research, a series of new terms has emerged to describe the phenomena unique to the presence of plastic-based materials in nature. In this short note, we bring together disparate neologisms into a single lexicon with the aim to encourage use of a unified vocabulary to describe the new reality of ecological, chemical, and geological systems in the age of plastics.